Participation in a multicomponent lifestyle intervention for people with obesity improves glycated hemoglobin (HbA1c) - Høgsholt, Mathias; Kierkegaard-Brøchner, Signe; Sørensen, Ulla Milther; Lange, Lene Bastrup; Mortensen, Lene Sundahl; Bruun, Jens Meldgaard (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: Obesity is associated with compromised glucose metabolism. Hence, it is of interest to investigate if the lifestyle interventions used in the LIBRA-cohort, which aimed at not only weight loss, but also patient well-being, could also help obese patients improve glucose metabolism by evidence of reduced HbA1c. The aim of the study was to retrospectively investigate if patients who were referred to a lifestyle intervention for obesity, were able to alter HbA1c. Research Design and Methods: Patients with a BMI≥30 undergoing a 6-month lifestyle intervention, who also complete physical and mental health surveys and whose baseline and 6month blood samples were available, were included in the analysis. For changes in HbA1c and body weight a clinically relevant change of 5≥mmom/mol and 5%≥, respectively, was chosen.Participants were divided into groups according to their baseline HbA1c level: "Diabetes": HbA1c of ≥6.5% (≥48 mmol/mol), "Prediabetes": HbA1c of 5.7% to 6.4% (39-47.99 mmol/mol) or "Normal" HbA1c <5.7% (<39 mmol/mol). Results: 180 patients met the stated inclusion criteria and these patients were divided into groups (median age (25 th ;75 th quartile): Diabetes: n=47, age 54 (43;60), 51% women, Prediabetes: n=68, age 60 (50;66), 71% women and Normal: n=65, median age 61 (50;66), 85% women. Significant reductions were found in all three groups and specifically in the diabetes group HbA1c was reduced (mean [95%CI]) -5[-8;-2] mmol/mol from baseline to the end of the intervention. Furthermore, 35% of patients with pre-diabetes normalized their HbA1c (<39) and 30% patients with diabetes reduced their HbA1c <48. All groups had clinically relevant (≥5%) reductions in body weight (p<0.01). There was an association between body weight reduction and HbA1c reduction in the diabetes group (p<0.01). All groups reported improvements in physical health (p<0.01). Conclusion: In this retrospective cohort study, all patients achieved clinically relevant weight loss after participation in the lifestyle intervention and obese patients with diabetes achieved clinically relevant reductions in HbA1c after 6-months. More than 1/3 of patients with pre-diabetes normalized their HbA1c.